(untitled) (PANGEEA, 2025)
The Complex Râpa Roşie Natural Reserve is a geologically and botanically rich site in Alba County along the right bank of the Secaş River. It features red sandstones and conglomerates shaped into a dramatic ’cathedral natural’ landscape and hosts European plant species, including several rare taxa near extinction. The reserve protects diverse habitats with endemic and rare species such as Cephalaria radiata, Onosma viride, Ephedra distachya, Cypripedium calceolus and Quercus pubescens, within a continental biogeographic context. Declared a natural reserve in 1950, it now covers 43 hectares and is part of conservation planning efforts in the region.